Application of operational car crew universal speed stenogram - Градусов Володимир Олексійович (Volodymyr Gradusov); Рибак Олег Юрійович (Oleg Rybak); Виноградський Богдан Анатолійович (Bohdan Vynogradskiy); Музика Федір Васильович (Fedir Muzyka) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: experimentally to check up possibility and efficiency of application of operative cars of universal speed shorthand records of unknown roads crews. Materials and Methods: theoretical analysis and generalization, pedagogical supervisions, pedagogical experiment, methods of mathematical statistics. In research took part 20 professional crews road patrol State Automobile Inspectorate, in all 40 persons, up-diffused on 2 groups for 10 crews: experimental and control. Results: application of methods of universal speed shorthand record of СД an experimental group allowed to shorten time-of-flight of segment of control distance on 7,37%. Conclusion: the results of pedagogical experiment at participation of professional crews road patrol State Automobile Inspectorate on official cars in the contention terms of the real route testify to possibility and efficiency of application of operative cars of the special setting of universal speed shorthand records of unknown roads crews during their professional activity.